2016
DOI: 10.1590/1980-5497201600030009
|View full text |Cite
|
Sign up to set email alerts
|

Carga viral comunitária do HIV no Brasil, 2007 - 2011: potencial impacto da terapia antirretroviral (HAART) na redução de novas infecções

Abstract: The approach presented in this study indicates the existence of clusters with high concentrations. The use of Kernel in the identification of clusters proved to be a good tool for exploratory analysis, enabling the risk identification in certain geographic areas without the usual political and administrative divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
3
0
4
Order By: Relevance
“…This fact points to the influence of the heterogeneity of Brazilian regions and states on the epidemiological behavior of certain diseases that suffer from their SDH. A mapping study of the circulating volume of HIV/AIDS in the country also revealed the heterogeneity of the infection among Brazilians, with areas of concentration of the community viral load between the untreated individuals in the Northeast Region compared to the Center-South Region 16 . It is considered, therefore, that the area of the studied municipality is heterogeneous and may present greater variability in the distribution of indicators and, consequently, in AIDS rates.…”
Section: Spatial Correlationmentioning
confidence: 99%
“…This fact points to the influence of the heterogeneity of Brazilian regions and states on the epidemiological behavior of certain diseases that suffer from their SDH. A mapping study of the circulating volume of HIV/AIDS in the country also revealed the heterogeneity of the infection among Brazilians, with areas of concentration of the community viral load between the untreated individuals in the Northeast Region compared to the Center-South Region 16 . It is considered, therefore, that the area of the studied municipality is heterogeneous and may present greater variability in the distribution of indicators and, consequently, in AIDS rates.…”
Section: Spatial Correlationmentioning
confidence: 99%
“…A síndrome da imunodeficiência adquirida (AIDS) é originada pelo vírus da imunodeficiência humana (HIV), sendo o curso natural da doença caracterizado pela redução dos linfócitos T CD4 nos indivíduos infectados; o que, em consequência reduz a imunidade e os torna propensos à graves doenças oportunistas (Barros et al, 2007;Sousa et al, 2016). Pessoas vivendo com HIV/Aids (PVHIV) constituem um público vulnerável, tanto no aspecto biológico, quanto no aspecto social, por isso são suscetíveis a apresentar insegurança alimentar e nutricional em diferentes partes do mundo (Anema et al, 2011;Medeiros et al, 2017;Costa et al,2018;Weiser et al, 2011).…”
Section: Introductionunclassified
“…A síndrome da imunodeficiência adquirida (AIDS) é originada pelo vírus da imunodeficiência humana (HIV), sendo o curso natural da doença caracterizado pela redução dos linfócitos T CD4 nos indivíduos infectados; o que, em consequência reduz a imunidade e os torna propensos à graves doenças oportunistas (Barros et al, 2007;Sousa et al, 2016). Pessoas vivendo com HIV/Aids (PVHIV) constituem um público vulnerável, tanto no aspecto biológico, quanto no aspecto social, por isso são suscetíveis a apresentar insegurança alimentar e nutricional em diferentes partes do mundo (Anema et al, 2011;Medeiros et al, 2017;Costa et al,2018;Weiser et al, 2011).…”
Section: Introductionunclassified